Pengaruh Pendekatan Matematika Realistik terhadap Kemampuan Berpikir Kreatif dan Koneksi Matematis Siswa - Durachman, Durachman; Cahyo, Edo Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2020)
Mathematics is often regarded as a boring subject, meaningless and less related to daily life. The teacher can use a variety of learning approaches that are interesting and make students more focused on paying attention and understanding the subject matter. The realistic mathematics approach in this study is used as a way to improve students' abilities especially in mathematics. The research method used is quasi-experimental with a non-equivalent control group. The population in this study were Madrasah Ibtidaiyah Negeri students in Bandung and Madrasa Ibtidaiyah Negeri Sumedang City. The results showed that the ability to think creatively and mathematical connections of students in the experimental class were better than students who obtained conventional mathematics learning. In addition, students' responses to mathematics learning using a realistic mathematical approach were interpreted as good, this is based on the results of a questionnaire that 86.08% of students were in the experimental class.